2006
DOI: 10.1111/j.1600-0722.2006.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interleukin‐10 on gene expression of osteoclastogenic regulatory molecules in the rat dental follicle

Abstract: The aim of this study was to determine the effect of interleukin-10 (IL-10) on the gene expression of osteoclastogenic regulatory molecules in rat dental follicle cells. Interleukin-10 is an anti-inflammatory cytokine that inhibits alveolar bone resorption, but the molecular basis for this is unknown. Alveolar bone resorption is required for tooth eruption and the dental follicle functions to regulate the osteoclastogenesis needed for eruption. It does this by regulating its expression of receptor activator of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 48 publications
1
56
0
4
Order By: Relevance
“…This may be consistent with the recent report that Th17 cells differentiated by the combination of TGF-␤1 and IL-6 produce not only IL-17 but also IL-10 and therefore that these Th17 cells are not able to mediate pathogenic function [37]. Indeed, IL-10 was previously reported to inhibit bone resorption by up-regulating the expression of osteoprotegerin (OPG), which is a natural antagonist of RANKL, while down-regulating expression of RANKL and colony-stimulating factor-1 (CSF-1) [38]. IL-27 also has an ability to induce IL-10 production (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…This may be consistent with the recent report that Th17 cells differentiated by the combination of TGF-␤1 and IL-6 produce not only IL-17 but also IL-10 and therefore that these Th17 cells are not able to mediate pathogenic function [37]. Indeed, IL-10 was previously reported to inhibit bone resorption by up-regulating the expression of osteoprotegerin (OPG), which is a natural antagonist of RANKL, while down-regulating expression of RANKL and colony-stimulating factor-1 (CSF-1) [38]. IL-27 also has an ability to induce IL-10 production (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…In vitro work in human and rat dental cells has demonstrated that IL-10 has antiosteoclastogenic properties by means of increasing OPG and decreasing RANKL mRNA expression, and the high levels of IL-10 observed in the +Inc/-Abx group may contribute to unexpectedly low RANKL production. 35,36 However, it is also possible that analysis of the membrane does not fully represent the profile of RANKL expression. Previous in vitro work in human and murine osteoblasts has shown that RANKL is upregulated in response to S. aureus infection, 18,19,37 and other studies have indicated that osteocytes, as opposed to osteoblasts or bone marrow stromal cells, are the dominant source of RANKL.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 directly suppresses osteoclast formation by reducing nuclear factor of activated T cells, cytoplasmic 1 (NFATc1) expression and its translocation to the nucleus (133) and by suppressing c-Fos and c-Jun (134). Indirectly IL-10 has been shown to modulate osteoclast formation by increasing gene expression of OPG and decreasing RANKL gene expression in dental follicle cells (135). …”
Section: Immune Cytokines and Bonementioning
confidence: 99%